(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: As the incidence of medical emergencies is rising, the demand of the knowledgeable and skilled personnel is also needed. It is important for every person to be competent enough to tackle all the emergency situations anywhere. First aid training helps to make a person able to give actual immediate care and safety awareness. The objective of the study is to assess the effectiveness of first aid training program in term of knowledge and skill among school teachers. Methodology: A Quasi-Experimental study following one pre-test post-test design was used. Participant’s data was collected from 105 school teachers from 12 schools (9 govt. and 3 private) using Total enumerative sampling and the schools were conveniently selected. Knowledge and skills were assessed by using structured knowledge questionnaire and observational checklist respectively. Conclusion: Data was analyzed using SPSS 16. The t test analysis showed a significant difference before and after the administration of first aid training program in term of knowledge(t=37.05 and p= 0.001)and skills (t=84.485 and p=0.000) at 0.05 level of significance. There was significant association of pre-test knowledge scores with educational status of school teachers.